Class of rational surfaces in P^4 - Voica, Christian (Mathematica Scandinavica, 2003)
In this paper, we obtain a complete classification of all rational surfaces embedded in P^4 so that all their exceptional curves are lines. These surfaces are exactely the rational surfaces shown by I.Bauer to project isomorphicaly from P^5 from one of their points, although no a priori reason is known why such a surface should be projectable in this way.